Unmasking the Hidden Threat: Post-COVID-19 Ischemic Stroke in a Young Adult - Ali Abdullah AlAseeri (International Journal of Biomedicine)
As of February 2024, over 774 million confirmed cases of COVID-19 and more than seven million deaths have been reported globally. Severe complications from COVID-19, such as cerebrovascular events, are prevalent, with research indicating that cerebrovascular accidents (CVAs) can occur in up to 6% of COVID-19 patients. This study presents a case of ischemic stroke in a 28-year-old male with no known risk factors, occurring 14 days after a COVID-19 infection. The patient's neurological examination revealed significant weakness in the right upper and lower limbs. Magnetic resonance imaging (MRI) findings were consistent with an acute ischemic stroke. The diagnosis of ischemic stroke was based on clinical symptoms and radiological findings. Cardiovascular evaluation did not find characteristic risk factors. SARS-CoV-2 IgG antibodies tested positive, indicating previous infection. This case underscores the importance of considering COVID-19 as a potential precipitating factor for ischemic stroke, even in young individuals without other vascular risk factors.